SECONDARY STUDENTS’ PARTICIPATION THROUGH EDMODO IN LEARNING SPEAKING WITH FLIPPED CLASSROOM - Marlisha Nisa Fatur Rahma; Fauzi Miftakh; Mansyur Srisudarso (Academy of Education Journal, 2023)
This study aims to determine the extent to which students understand English learning by using Edmodo in Flipped classroom media. To find out students' experiences in speaking skills, there are many features that can be used or utilized by Edmodo in Flipped classroom. The method used is Narrative inquiry with a qualitative approach. The sample used in this study was only 3 students taken from one class. The data analysis used consisted of data reduction, data display, and conclusion. First, Emodo media is very helpful in the online learning process. With Edmodo media, students can easily access and carry out learning activities, especially discussing speaking skills in the Flipped classroom. Second, for the past 1 year several schools have implemented a flipped classroom system where students are required to take part in online and offline teaching and learning activities. And finally, Edmodo media can make students independent in learning English. Students can learn on their own without the help of a teacher when they understand the use of Edmodo, students can immediately practice their speaking skills with the features available on Edmodo.